Bean crop cycle records from technology validation areas and seed banks - Huang, Si-Dun; Kuo, Chin-Chien; Peng, Yuan-Ching; Aguilar, Andrés; Siles, Pablo; Rivera Palacio, Juan Camilo; Dorado, Hugo (International Center for Tropical Agriculture, 2020)
This dataset contains 721 crop cycles for beans in 9 departments of Nicaragua that were collected in the period 2016 – 2019. Each location was georeferenced. Variables such as cultivar, planting practices, harvest date, region, and precipitation were also recorded. The weather and soil variables were extracted from INETER (Instituto Nicaragüense de Estudios Territoriales), GLDAS (Global Land Data Assimilation System) and Chirps